Na2CO3-Catalyzed O-Acylation of Phenols for the Synthesis of Aryl Carboxylates with Use of Alkenyl Carboxylates - Zhou, Xiao-Yu; Chen, Xia (Synlett, 2018)
Inorganic base-catalyzed O-acylation of phenol and its derivatives has been developed. The procedure provides an efficient catalysis system for the preparation of aryl carboxylates with alkenyl carboxylates as acyl reagents. The reaction proceeded smoothly by using Na2CO3 as the catalyst in MeCN to produce the corresponding aryl carboxylates in good to excellent yields.
Keywords: acylation; phenols; aryl carboxlates; alkenyl carboxylates; catalysis